Development of E-Assessment Instruments for Monitoring Early Childhood Memorization of The Qur'an through Istima' Teaching Materials - Wijayanthi R, Tika; Panji Yudha, Rivo (Kirana Publisher (KNPub), 2024)
This study aims to develop an e-assessment instrument for monitoring the ability to memorize the Qur'an in early childhood through Istima's teaching materials. Using the 4-D development model (Define, Design, Develop, Dissemination), this research was conducted at Al Hisan Kindergarten, Bekasi, with research subjects aged 5-6 years. The results showed that the Istima' method is effective for children who have not mastered the hijaiyah letters; no significant differences were found in its application in different classes, and there are differences in Arabic pronunciation and speed of memorizing surahs. The results of the validation of this e-assessment product (Silentdra Assessment) are valid and reliable. The results of this validity consist of a trial of 3 validators, namely media expert validators of e-assessment products (Silentdra Assessment), who get good qualification validity test results. As well as the results of the validity of the assessment expert on this e-assessment (Silentdra Assessment) product get good qualification results. Also the results of the Qur'an validator of the e-assessment product (Silentdra Assessment), which get good qualification validity results. The results of this reliability show the average agreement between raters of 0.125, while for the person rater the consistency is 0.932, which means it has high stability.